Land and man - "Alagh, Yoginder K." (New Delhi, 1996)
In this book Yoginder Alagh, one of India's most experienced planners and policy makers, unfolds the evolution of his thinking on issues ranging from agroclimatic planning, economic reform for agriculture and rural development and large irrigation projects including Sardar Sarovar, to energy policies, agricultural research, bio-technology and recent estimates and controversies on poverty. These essays were first published in prestiguous journals in India and abroad or were well known invited lectures. Alagh has written a special introduction to this volume on the next stage of agroclimatic planning in terms of policies in the post Gatt phase, as also looking back. on the Rio Conference from the vantage point of the Hague declaration organized by Jan Pronk and Mahbubul Haq of which he was also a signatory-and the exercises of the World Bank.
Keywords: Sustainable development